How do researchers generate scientific and societal impacts? Toward an analytical and operational framework. (9th March 2018) - D'Este, Pablo; Ramos-Vielba, Irene; Woolley, Richard; Amara, Nabil
Abstract: Models of research systems increasingly emphasize collaborations between networks of heterogeneous actors, to both produce knowledge and formulate interdisciplinary responses to societal challenges and market needs. In this context, researchers' goals and practices are required to satisfy professional requirements for new scientific findings and societal demand for relevant knowledge. Researchers may need also to find ways to reconcile tensions between these two missions. This article proposes an analytical and operational framework that incorporates individual, organizational and process-context factors to explain distinct configurations of scientific and societal impacts from research. The framework emphasises the role of productive interactions with different nonacademic actors as a mechanism for reconciling the scientific and societal missions of research.